Tecnologias de tratamento de resíduos agropecuários como indutoras à economia circular no agronegócio. - Hollas, Camila Ester (2022)
A circular-based economy aimed at using resources, especially with the insertion of waste in the value chain with a focus on energy use, can help reduce environmental pressure and mitigate dependence on non-renewable sources. Given this, the productive sectors have increasingly invested in technologies to promote the decarbonization of the activity, mitigating environmental damage without harming the development of the chain. However, these technological routes present certain implementation barriers; an integrated solution that allows maximizing the use of waste, thus reducing costs, is still a challenge. Therefore, the present study aims to understand and deepen the studies of the interconnection between anaerobic digestion and nitrogen removal processes, consequently allowing the potential for biogas production from agricultural and livestock waste and water reuse. For this purpose, different configurations of treatment systems were analyzed according to different scenarios to evaluate the economic, technical, and environmental viability of these alternatives, seeking to maximize environmental sustainability in the swine production chain, allied to the circular economy, to recover treatment investments. Initially, an investigation regarding the optimization conditions of swine waste management was conducted, focusing on the solid-liquid separation stage, which is fundamental for the interconnection of the treatment systems. This study evaluated the effects of storage time on sieving and sedimentation efficiency, in addition to the environmental and energy consequences of management strategies. From this study, it was possible to verify that the reduction of the storage time contributed significantly to the improvement of the solids separation process since, after five days of storage, the sieving efficiency reduced by 80 ± 0.5%, increasing the sludge volume in sedimentation to 51 ± 0.1%. Furthermore, in environmental terms, the reduction in storage promoted a 10.7% reduction in the global warming potential of the management scenario, improving the energy performance, with the generation of up to 4.5 kWh m-3 of treated waste. Based on these estimates, the scenarios were expanded, having as reference the SISTRATES® (Swine Farm Effluent Treatment System), composed of 3 modules for energy use (bio module), nitrogen removal (N module), phosphorus removal and recovery (P module); three configurations were simulated and evaluated as to their technical, environmental, and economic feasibility. Based on the performance of the units in relation to the inputs and outputs, by means of economic indicators and life cycle studies, it was possible to highlight the importance of prioritizing the routes of energy use, for the viability of adopting treatment systems. In a circular economy context, SISTRATES® proved to be efficient in transforming effluents into energy, nutrients, and reuse water, presenting the best performance in cascade (high efficiency of the modules 75 ± 24%), added to the lower emission of greenhouse gases (2.16E+01 kgCO2eq) and the best economic indicators (cost-benefit of 1.82). Thus, the adoption of the treatment technologies described in this study guides waste management with value addition and minimization of environmental damage, contributing to the decarbonization of the swine production chain towards the circularity of production processes.